The Establishment of the Idrisid State in Al-Maghrib Al-Aqsa (Morocco) (172-375 AH / 788-985 AD) - Toheri, Amal Mohamed (Arab Journal for Sciences and Research Publishing, 2022)
This research aims to trace the path of Idris bin Abdullah in the East, and the reasons that prompted his departure to Al-Maghrib Al-Aqsa (Morocco) in particular, the stability in Volubilis (Walīlī), and then the emergence of the political entity known as the Idrisid State. This study is based on the descriptive, analytical and critical scientific method by extrapolating historical narratives, analyzing their contents, and comparing all their details. The research was divided into an introduction, several headings, and a conclusion. The introduction includes the topic, importance, and sources of the research. The research chapters are divided into: The Path Towards the Establishment of the State”; “Stabilization in the City of Volubilis (Walīlī),” and then “The Establishment of the Idrisid State.” The conclusion includes all the findings of the research. The research concluded: 1- The establishment of the Idrisid State went through several stages, beginning with the separation of Idris bin Abdullah from his brothers who aspired to power by crossing into Egypt after the Battle of Fakhkh, and leaving Egypt without approaching the representatives of the Abbasid authority in it. 2- Passing through Al-Jurayd Road in order to continue hiding until reaching Volubilis (Walīlī) and settling in part of it. 3- Idris bin Abdullah did not cause a change in political life. He sufficed with the part that he had taken from Volubilis (Walīlī). Thus, his success lies in not clashing with the political reality. 4- The sayings about the vast extension of the Idrisid State are completely false.